Prevalence of Depression in Animal Model of High Fat Diet Induced Obesity - Muhammad Farhan; Hamna Rafiq; Hira Rafi (Journal of Pharmacy and Nutrition Sciences, 2015)
The prevalence of obesity is substantially increased in developing countries and it is considerably associated with type 2 diabetes (T2DM), dyslipidemia, and hypertension. These symptoms are clustered to form metabolic syndrome. In accordance with the Researchers opinion, obese people are more likely to suffer from depression, a mental affliction that appears due to chronic stress, disturbs thoughts, behavior, and feelings. It has been addressed that the physiological impairments which are undergoing due to obesity can affect the metabolic activities which in turn give impact on brain and affect it’s functioning, because obesity itself seems to constitute a chronic stressful state thus, exacerbates the risk of depression. Present study intended to illuminate the anticipated links between obesity and stress. To make possible the study, animal model of obesity was accomplished by subjecting the Albino wistar rats with energy-dense diet (high fat diet) for 5 weeks; later on, chronic mild stress paradigm was implemented along with high fat feeding for 2 weeks. As expected, high fat feeding increased the adiposity in rodents. Obese animals presented the depressive symptoms more prominent than normal fat feeding rats. Present findings suggest that obesity could increase the depressive symptoms potentially involve in the recruitment of depression.